ANALISIS GERAKAN MASSA TANAH AKIBAT PERUBAHAN MUKA AIR TANAH - , Novita Landa Lebang ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Toll Road of Semarang-Solo, based on its topographical and geological condition is unstable and frequently has creep ground movements. The toll road construction is on a soil layer dominated by clay layers and clayshale, a type of soil with very easily decaying characteristics if it is exposed due to excavation during the construction process. The poor quality of clayshale layers may cause the movement of embankment construction and road construction. The research studied the behavior of lateral deformation and slope safety figures in the construction process as well as during the service period using Plaxis program based on topographic data, investigation data and field instrumentation. Once the results of validation with its suitability of movement pattern to horizontal direction on the slope is detected, then a simulation can be performed with different models, i.e. based on the strengthening effect of bored piles, the effect of loading (traffic and earthquake), as well as ground water level (rainy season, dry season and maximum water level that can be tolerated by a slope which has been reinforced by the bored piles). Horizontal movement from the simulation results was reviewedat the inclinometer location. Research result shows that the original slope is in anunstable condition with a horizontal displacement of 0.32 meters and its safe figure is 1.19. Soil mass movement on slopes was triggered by the weathered clayshale layer which is the weakest layer of all soil layers at Sta. 5+739. The pattern of slope soil mass movement is a flow with rotational motion where the slip plane tends to curved on a weathered clayshale layer. Once the construction process (excavation, embankment and strengthening bored piles)is conducted, the slope has horizontal deformation of 0.43 meters. With a secure rate 1,247. Once the simulation of traffic load and earthquake load is performed, the horizontal deformation is 0.80 meters with secure rate of 1.23. During rainy season, the slope condition is more unstable due to the increased pore water pressure in the slope that increases the load which also increases the shear stress. Simulation with a trial and error on the fluctuations of groundwaterwas conducted to determine maximum ground water level that can be accepted by the construction with secure rate of 1.20, it obtained the maximum height limit is 4.52 meters rise from the ground water levels on a normal condition, with horizontaldeformation of 0.69 meters.